Double gate operation of metal nanodot array based single electron device - Takayuki Gyakushi; Ikuma Amano; Atsushi Tsurumaki-Fukuchi; Masashi Arita; Yasuo Takahashi (Scientific Reports, 2022)
Abstract Multidot single-electron devices (SEDs) can enable new types of computing technologies, such as those that are reconfigurable and reservoir-computing. A self-assembled metal nanodot array film that is attached to multiple gates is a candidate for use in such SEDs for achieving high functionality. However, the single-electron properties of such a film have not yet been investigated in conjunction with optimally controlled multiple gates because of the structural complexity of incorporating many nanodots. In this study, Fe nanodot-array-based double-gate SEDs were fabricated by vacuum deposition, and their single-electron properties (modulated by the top- and bottom-gate voltages; V T and V B, respectively) were investigated. The phase of the Coulomb blockade oscillation systematically shifted with V T, indicating that the charge state of the single dot was controlled by both the gate voltages despite the metallic random multidot structure. This result demonstrates that the Coulomb blockade oscillation (originating from the dot in the multidot array) can be modulated by the two gates. The top and bottom gates affected the electronic state of the dot unevenly owing to the geometrical effect caused by the following: (1) vertically asymmetric dot shape and (2) variation of the dot size (including the surrounding dots). This is a characteristic feature of a nanodot array that uses self-assembled metal dots; for example, prepared by vacuum deposition. Such variations derived from a randomly distributed nanodot array will be useful in enhancing the functionality of multidot devices.